Photo-oxidation of EPDM/layered double hydroxides composites: Influence of layered hydroxides and stabilizers (eXPRESS Polymer Letters)
The photo-oxidation of ethylene propylene diene monomer (EPDM)/ layered double hydroxide (LDH) composites as well as EPDM/LDH with stabilizers is studied under accelerated UV irradiation (λ≥290 nm) at 60°C for different time intervals. The development of functional groups during oxidation was monitored by FT-IR spectroscopy. The photodegradation of the pristine polymer and composites take place and the increase in hydroxyl and carbonyl groups with irradiation times, was estimated. EPDM filled LDH showed higher degradation rate than pristine EPDM, while in acidic medium EPDM/LDH showed almost equal degradation as in isolated conditions. These results show the advantages of LDHs as a filler as well as an acid killer. The effect of stabilizers is very less because of their concentration in comparison of LDH.